2021
DOI: 10.3390/toxics9090214
|View full text |Cite
|
Sign up to set email alerts
|

The Bladder Is a Novel Target of Developmental Polychlorinated Biphenyl Exposure Linked to Increased Inflammatory Cells in the Bladder of Young Mice

Abstract: Bladder inflammation is associated with several lower urinary tract symptoms that greatly reduce quality of life, yet contributing factors are not completely understood. Environmental chemicals are plausible mediators of inflammatory reactions within the bladder. Here, we examine whether developmental exposure to polychlorinated biphenyls (PCBs) leads to changes in immune cells within the bladder of young mice. Female mice were exposed to an environmentally relevant mixture of PCBs through gestation and lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Changes in collagen fibril distribution and remodeling in the prostate and bladder extracellular matrix have been shown to occur in an aged mouse model developmentally exposed to dioxin [ 8 ]. We have recently shown that developmental PCB exposure can decrease bladder collagen density in young mouse offspring [ 25 ]. Therefore, we wanted to determine whether developmental exposure to PCBs can alter collagen density within the prostate in young adult mouse offspring and whether these changes coincide with observed changes in prostate wet weight ( Figure 1 ) or previously reported voiding dysfunction [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in collagen fibril distribution and remodeling in the prostate and bladder extracellular matrix have been shown to occur in an aged mouse model developmentally exposed to dioxin [ 8 ]. We have recently shown that developmental PCB exposure can decrease bladder collagen density in young mouse offspring [ 25 ]. Therefore, we wanted to determine whether developmental exposure to PCBs can alter collagen density within the prostate in young adult mouse offspring and whether these changes coincide with observed changes in prostate wet weight ( Figure 1 ) or previously reported voiding dysfunction [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we observed that developmental PCB exposure at the 1 mg/kg treatment group decreased anterior prostate collagen density in 6-week-old mouse offspring. Additionally, we have shown PCBs can lead to decreased collagen density in the bladder of developmentally exposed mice but only at the 0.1 mg/kg treatment group and predominantly in female mice [ 25 ]. Together this adds to the growing body of evidence that dioxin, as well as PCBs, can interfere with the extracellular matrix in the bladder and the prostate in a dose and sex-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCBs are also capable of altering the physiological antiviral cellular response [86]. In an in vivo mouse model, PCB promoted an alteration of collagen in the female bladder compared to the male one, indicating an inflammatory event that results in the impairment of immune system functions [87]. Moreover, studies from PCB-exposed populations have revealed DNA methylation differences in CpG sites with effects in oestradiol CpG site sizes and affecting the immune system [88].…”
Section: Polychlorinated Biphenyls (Pcbs)mentioning
confidence: 99%
“…(in vivo and ex vivo) [86] DNA methylation differences in PCBexposed populations Human PBMCs (ex vivo) [87] PBDEs Liver, kidney, gut, and thyroid toxicity…”
Section: Reduction Both Of Antibody's Production By B Cell and Cytoto...mentioning
confidence: 99%